Deadline-Chasing in Digital Health: Forecasting EMR Adoption Dynamics and Regulatory Impact in Indonesian Primary Care - Satrio, Suryo; Aqid, Bukhori Muhammad (Journal of Indonesian Health Policy and Administration, 2026)
Indonesia is accelerating digital health adoption under Minister of Health Regulation No. 24/2022, which mandates the use and integration of Electronic Medical Records (EMRs) with SATUSEHAT. However, evidence on how quickly primary health care facilities (Fasilitas Kesehatan Tingkat Pertama – FKTP) are adopting EMRs and what the adoption curve looks like remains limited. Survey findings also suggest key barriers and enablers, including security and data migration concerns, as well as human resource and infrastructure constraints. This observational study used provider-network data from a single EMR vendor. Key measures included cumulative registered facilities, monthly registrations, same-month activation (total_active/monthly inflow) as a proxy for onboarding readiness, and the estimated national pool of eligible FKTPs. The study applied descriptive analysis, logistic growth modeling, and Autoregressive Integrated Moving Average (ARIMA) forecasting for short-term projections. Over 39 months, cumulative registrations increased from 2 to 3,803 facilities. Same-month activation remained consistently high (median 0.969, IQR 0.744–0.999). By June 2025, the vendor network captured a 10.3% share of the estimated eligible FKTP pool (3,803/36,784). Logistic modeling suggested convergence to a carrying capacity of approximately 4,034 facilities (95% CI 3,953–4,115), while ARIMA projected around 4,030 facilities by December 2025 (95% CI 3,467–4,593). EMR adoption continues to increase, with rapid activation after registration, although growth slows over time. Localized increases near enforcement milestone windows are consistent with “deadline-chasing” behavior. Policy makers and vendors should combine deadline calendars with streamlined onboarding, secure migration support, clear technical-support SLAs, and region-specific interventions to address workforce and infrastructure gaps.